Gold Value with Tradable and Non-Tradable Goods in a Multi- Country Growth Model with Free Trade - Wei-Bin Zhang (Economic Review: Journal of Economics and Business, 2016)
The purpose of this study is to examine gold price in global markets. We introduce gold into a general dynamic equilibrium growth model with multiple countries and free trades between countries. The model is developed by integrating the Solow growth model, the Uzawa two-sector growth model, and the Oniki-Uzawa trade model within a comprehensive framework. The model is built for any number of national economies and each national economy consists of one tradable and one non-tradable sectors. National economies are different in population, technologies, propensities to save, propensity to use gold, and propensities to consume. We show that the dynamics of the J-country world economy can be described by J differential equations. We simulate the model to demonstrate the existence of an equilibrium point, motion of the dynamic system, and (local) stability of the equilibrium point. We also demonstrate how changes in the propensities to use, the populations, the propensities to save, and the total factor productivities affect global economic development.
Keywords: O4; F11; 330; trade pattern; gold value; tradable and non-tradable; economic growth; wealth accumulation